Effect of tenofovir, an antiretroviral drug, on hepatic and renal functional indices of Wistar rats: protective role of vitamin E (2012)
Tenofovir (TFR) is a nucleotide reverse transcriptase inhibitor with activity against human immunodeficiency virus. We studied the effect of TFR administered to Wistar rats on hepatic and renal function markers and the possible modulatory role of vitamin E (Vit E). The study consists of four groups of six rats each. The fi rst group served as control, the second group received TFR at 50 mg/kg/day for 4 weeks, third group received TFR and Vit E, and the last group received Vit E alone. TFR administration caused a significant (p< 0.05) increase in the levels of serum urea, creatinine, urinary glucose, and protein by 65 % , 51 % , 88 % , and 79 % , respectively, relative to controls. This was followed by a signifi cant (p< 0.05) reduction in creatinine clearance of TFR-treated rats. There were no significant differences (p > 0.05) in the activities of serum aminotransferases,, glutamyl transferase and alkaline phosphatase in TRF-treated rats relative to controls. TFR administration caused a marked elevation of malondial dehyde (MDA; index of lipid peroxidation) in the animals. Specifi cally, serum, hepatic, and renal MDA levels increased by 75 % , 90 % , and 102 % , respectively. TRFtreated rats had signifi cantly (p < 0.05) reduced activities of renal catalase, glutathione- S -transferase, and superoxide dismutase. Supplementation of Vit E ameliorated TFR-induced effects by decreasing the levels of MDA and enhancing the activities of renal antioxidative enzymes. The biochemical data were supported by histopathological fi ndings from the slides.TFR increased oxidative stress and altered kidney function markers in the rats, whereas supplementation of Vit E attenuated these effects.